Pelatihan Literasi Digital untuk Meningkatkan Peran Kolaboratif Orangtua dan Guru PAUD dalam Mendampingi Anak - Amanda, Rizki Surya; Hasni, Uswatul; Ismiatun, Asih Nur; Rosyadi, Akhmad Fikri; Muazzomi, Nyimas (LPPPM STAI Darul Hikmah Bangkalan, 2025)
Digital literacy has become one of the essential skills to strengthen in the 21st century. Limited digital literacy among parents or caregivers often results in insufficient supervision and guidance for children when using digital devices. This situation places children at greater risk of exposure to harmful online content, which may hinder their overall growth and development. This community engagement program was designed to provide training on digital literacy for parents, teachers, and school principals, enabling them to collaborate more effectively in guiding children’s digital activities. A total of 30 participants took part in this program. These three participant groups were intentionally selected to foster stronger collaboration and synergy between home and school environments, ensuring children receive appropriate support. The program was carried out in four stages: identifying partner characteristics and needs, developing implementation methods, conducting training activities, and evaluating the program’s outcomes. The results indicate a significant increase in participants’ knowledge of children’s digital literacy, including safe and educational content selection, guidelines for responsible gadget use, and practical skills in using parental control applications to monitor and support children’s digital engagement